EVALUATION OF ANTIOXIDANT POTENTIAL OF CITRUS PEEL ESSENCE FROM CHLEF REGION (ALGERIA) - BENGAG. AMINE; ALLEM. RACHIDA (International Journal of Pharma and Bio Sciences, 2016)
The objective of the current study was to evaluate the antioxidant activity of Citrus peel essence by using DPPH radical scavenging activity and β- carotene test Methods The essence of four varieties of Citrus: C. Sinensis, C. paradisi, C. reticulata and C. aurantium were been extracted by cold expression, then the extract was analyzed to determine the chemical composition by Gas Chromatography coupled to Mass spectrophotometry (GC/MS). The antioxidant activity of Citrus essences was assessed by DPPH and β- carotene test comparatively to BHT and Quercetin. The results obtained demonstrated that the IC 50 of Citrus essences range from : 1,9068 ± 0,0912 μg ml-1 for Citrus reticulata, 6,2086 ± 0,0308 μg ml-1 for Citrus aurantium, 12,7662 ± 0,0736 μg ml-1 for Citrus paradisii, and 19,1567 ± 0,00499 μg ml-1 for Citrus sinensis, which were all lower than the lC50 of the synthetic antioxidants : Quercetin (IC50 15,9938 ± 0,01284 μg ml-1) and Butylhydroxyanisole (BHA) (IC50 21,9938 ± 0,01284μg ml-1). In conclusion it has been suggested that Citrus essences constituent a real source for natural antioxidant that can be used in several domain such as : pharmaceutics , culinary and food engineering.